2019
DOI: 10.1590/s1984-29612019058
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hemotropic Mycoplasma sp. in white-eared opossums (Didelphis albiventris) from Southern Brazil

Abstract: Opossums are marsupials from the New World of the genus Didelphis and known as synanthropic animals due to their proximity with human beings. To date, ‘Candidatus Mycoplasma haemodidelphis’ has been solely found infecting the North American opossum (Didelphis virginiana). Accordingly, the aim of this study was to screen eight white-eared opossums (Didelphis albiventris) from a public park in Maringa city, Paraná State, southern Brazil, for hemoplasma infection. Blood samples were taken from caudal venipuncture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…M. haematodidelphidis. These sequences were included in the same well-supported branch with one of the sequences detected in raccoons in the USA (Massini et al, 2019). Identical sequences have since been confirmed in 14 out of 43 white-eared opossums from urban forests in Mato Grosso do Sul (Gonçalves et al, 2020).…”
Section: Marsupialsmentioning
confidence: 56%
“…M. haematodidelphidis. These sequences were included in the same well-supported branch with one of the sequences detected in raccoons in the USA (Massini et al, 2019). Identical sequences have since been confirmed in 14 out of 43 white-eared opossums from urban forests in Mato Grosso do Sul (Gonçalves et al, 2020).…”
Section: Marsupialsmentioning
confidence: 56%
“…The 16S rRNA gene sequences showed that opossums were infected by a potentially novel hemotropic Mycoplasma sp. previously identified in white-eared opossums from two regions of Brazil (Massini et al, 2019;Gonçalves et al, 2020) and closely related to 'Ca. M. haemodidelphis'.…”
Section: Discussionmentioning
confidence: 86%
“…There has not been robust evidence to support the hypotheses that hemotropic mycoplasmas are truly vector-borne pathogens to date, although it is important to point out that white-eared opossums are frequently parasitized by C. felis fleas (Nascimento & Horta, 2014) and Amblyomma dubitatum ticks (Massini et al, 2019;Gonçalves et al, 2020), while the North American opossum are mainly infested by C. felis fleas and by the American dog tick Dermacentor variabilis (Durden & Wilson, 1990), for sharing habitats with domestic and other wildlife animals. A previous study has failed to detect hemoplasmas in A. dubitatum ticks parasitizing hemotropic mycoplasma-infected white-eared opossums (Gonçalves et al, 2020) Previous studies have found hemoplasma prevalence rates of 32.5% (Gonçalves et al, 2020) and 87.5% (Massini et al, 2019) in white-eared opossums from Campo Grande City, Mato Grosso do Sul State, and Maringá City, Paraná State, Brazil, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For example, opossums captured close to human dwellings have been reported harboring species of hard ticks (Amblyomma spp.) (Massini et al 2019;Bezerra-Santos et al 2020b), which are usually found in other wildlife species within forests areas of Brazil (Dantas-Torres et al 2010). Moreover, the relevance of opossums as potential disseminators of tick-borne pathogens has been suggested by studies on the exposure of these marsupials to tick-borne zoonotic pathogens, such as R. rickettsii, B. burgdorferi and Ehrlichia chaffeensis (Horta et al 2009;Castellaw et al 2011;Melo et al 2016).…”
Section: Ticks and Tick-borne Pathogensmentioning
confidence: 93%